PsycEXTRA Dataset 2007
DOI: 10.1037/e527342012-262
|View full text |Cite
|
Sign up to set email alerts
|

Bill Clinton on the Middle East: Perspective in Media Interviews

Abstract: A corpus of four TV and two radio interviews given by Bill Clinton

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They have found no such imbalance in the BBC coverage. More recently, Suleiman and O'Connell (2007) have pointed out Bill Clinton's perspective in media interviews, as shown in his way of referring to the Israeli and Palestinian points of view by designating them with first-personal and third-personal pronominals, respectively. Again, the we and they mentality prevailed -good guys and bad guys.…”
Section: Some Recent Research On Referringmentioning
confidence: 99%
See 1 more Smart Citation
“…They have found no such imbalance in the BBC coverage. More recently, Suleiman and O'Connell (2007) have pointed out Bill Clinton's perspective in media interviews, as shown in his way of referring to the Israeli and Palestinian points of view by designating them with first-personal and third-personal pronominals, respectively. Again, the we and they mentality prevailed -good guys and bad guys.…”
Section: Some Recent Research On Referringmentioning
confidence: 99%
“…It may be that Hillary Clinton simply wished to build camaraderie with her interviewers. Along these lines, Cohen (1987, p. 122 f.; see also Suleiman & O'Connell, 2007) has observed that interviewees use first names with their interviewers rhetorically to give the illusion that they are closer in position or perspective to the interviewers than they really are. One American journalist reported to Cohen regarding interviewees' use of first names: ''Sometimes people try to rub off against your credibility by showing some intimacy that is simply not there.''…”
Section: Some Recent Research On Referringmentioning
confidence: 99%